How much damage do serial homicide offenders wrought while the innocent rot in prison? A tabulation of preventable deaths as outcomes of sentinel events. Issue 1 (2nd January 2021) - Yaksic, Enzo; Bulut Allred, Tara; Drakulic, Christa; Mooney, Robyn; De Silva, Raneesha; Geyer, Penny; Wills, Angelica; Comerford, Caroline; Ranger, Rebekah
ABSTRACT: The criminal justice system has allowed serial homicide offenders (SHOs) to commit additional homicides by failing to identify them after their initial homicide. Recidivism has been possible in instances where the SHO benefited from the wrongful incarceration of an innocent person for one of their homicides. Data from the National Registry of Exonerations was utilized to tabulate the full extent of these sentinel events, defined as the number of deaths that could have been prevented. Additional research was conducted to identify where victims fell in the offender's killing sequence. This ancillary data revealed the number of victims whose deaths could have been prevented had the offender been apprehended earlier in their series of homicides. Sixty-two SHOs were responsible for 249 deaths, 114 of which were committed after an innocent person was incarcerated for the SHO's initial homicide. To prevent further loss of life, law enforcement must: act upon accurate information; lower the SHO evidentiary threshold; prevent personal bias from influencing investigative steps; obtain training in the behavior of SHOs; admit mistakes; and re-examine convictions if wrongdoing is suspected.